MODEL KOMUNITAS PRAKTEK BERBASIS MODAL SOSIAL UNTUK PENINGKATAN MUTU PENDIDIKAN KEWIRAUSAHAAN MASYARAKAT - Entoh Tohani; Sujarwo Sujarwo (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
This study aims to develop model of community of practice based on social capital for improving quality of the community entrepreneurship education and also to contribute the decision making process for community development, theory and practice development. The study used research and development approach which consisted of four steps: need assessment, designing of the conceptual model, and try out in limited field. Taking place in Yogyakarta Special Province, the study selected the community entrepreneurship education in Gunung Kidul Regency and the enterprise learning groups in Bantul Regency. In this study, data collection used interview, observation, documentation and questionare, and analysis of data used qualitative and quantitative technique. The result shows that it`s could be developed the model of community of practice based on social capital for developing the entrepreneurship education quality and also guidance for managing the model which was be validated. The other finding are actions of the model development could be able to encourage consciousness of the target groups to build, manage, and keep the community practice in their enterprise, motivated the target group to participate actively in their enterprise and find out new understanding and knowledge by held learning activities. So that, it is needs to implementation the community of practice based social capital model in developing community entrepreneurship education in future for continuing and controlling the quality.